The role of extracellular vesicle fusion with target cells in triggering systemic inflammation - Papareddy, Praveen; Tapken, Ines; Kroh, Keshia; Varma Bhongir, Ravi Kiran; Rahman, Milladur; Baumgarten, Maria; Cim, Eda Irem; Györffy, Lilla; Smeds, Emanuel; Neumann, Ariane; Veerla, Srinivas; Olinder, Jon; et al. (Nature communications, 2024)
Extracellular vesicles (EVs) play a crucial role in intercellular communication by transferring bioactive molecules from donor to recipient cells. As a result, EV fusion leads to the modulation of cellular functions and has an impact on both physiological and pathological processes in the recipient cell. This study explores the impact of EV fusion on cellular responses to inflammatory signaling. Our findings reveal that fusion renders non-responsive cells susceptible to inflammatory signaling, as evidenced by increased NF-κB activation and the release of inflammatory mediators. Syntaxin-binding protein 1 is essential for the merge and activation of intracellular signaling. Subsequent analysis show that EVs transfer their functionally active receptors to target cells, making them prone to an otherwise unresponsive state. EVs in complex with their agonist, require no further stimulation of the target cells to trigger mobilization of NF-κB. While receptor antagonists were unable to inhibit NF-κB activation, blocking of the fusion between EVs and their target cells with heparin mitigated inflammation in mice challenged with EVs.
Keywords: Biological Transport; myši; zánět; Extracellular Vesicles; signální transdukce; biologický transport; extracelulární vezikuly; Animals; Mice; Inflammation; zvířata; NF-kappa B; Signal Transduction